ANALISIS PERAN NELAYAN MUROAMI TERHADAP EKOSISTEM LAUT TAMAN NASIONAL KEPULAUAN SERIBU (STUDI KASUS DI SPTN WILAYAH III PULAU PRAMUKA TAMAN NASIONAL KEPULAUAN SERIBU) TAHUN 2021 - Jessica Islamiati (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2021)
Muroami nets are the main fishing gear for catching various reef fish with large nets and small hole nets made so that they can catch small fish in coral reefs. This muroami does not think long about catching which can result in increased pressure on reef fish resources in long-distance conditions. Based on Article 9 Paragraph 2 of Law Number 45 of 2009, a policy of fishing using muroami nets has been established which is illegal. This research method uses a qualitative approach. Data was collected by direct observation, interviews with informants, and documentation as evidence of the research that had been carried out in the SPTN Region III Pramuka Island, Seribu Islands. The results of this study explain that the use of this type of muroami net has been prohibited which has been strictly regulated by government policy and there are many suggestions and assistance from the agency to reduce the operation of muroami nets by providing assistance and marine cultivation. The implementation of this policy has an inhibiting factor, namely in fostering groups of fishermen who are not aware of the damage to marine ecosystems. The supporting factor in research is the awareness of using more than two mesh sizes